ANALYSIS SWOT OF COFFEE AT CV FRINSA AGROLESTARI - Rosalinda, S; Salsabila, Rike; Sumirat, Riska; Ratnaduhita, Astari (Universitas Veteran Bangun Nusantara, 2024)
Coffee (Coffea L.) is one of the plantation commodities that has a high economic value in Indonesia. One of the coffee producers in Indonesia is CV Frinsa Agrolestari in Pangalengan, West Java. CV Frinsa Agrolestari is a family company engaged in the coffee business, starting from nursery, planting, and processing coffee beans to breeding coffee varieties. The purpose of this research is to identify internal and external environmental factors to obtain alternative strategies for CV Frinsa Agrolestari. The research method used is the survey method with Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. Data on strengths, weaknesses, opportunities, and threats were obtained from the internal and external environment of CV Frinsa Agrolestari. Based on the analysis, it shows that CV Frinsa Agrolestari is in quadrant I (positive, positive). This position signifies a strong company. So the strategic recommendation given for CV Frinsa Agrolestari is progressive, meaning that the company is in prime and steady condition to continue to expand, enlarge growth, and achieve maximum progress. Keywords: CV Frinsa Agrolestari, External, Internal, Coffee, Quadrant I, SWOT.